Are Geographer’s Research Methodologies Really Poor? - Koirala, Hriday L (Tribhuvan University Journal, 2010)
Research methodology is closely associated with both philosophy and paradigm of a discipline. Paradigms are combinations of law, theory and methodology. Philosophy critically assesses the objectives of the explanation and how they are achieved. Theory is used to create the bases for the explanation. Therefore, it is utmost necessary to tie up theories/concepts, philosophy and methodology in an academic research. Most of the doctoral research works of Nepal in human geography are either entirely empiricist/positivist or unaware of these ’isms’ in geography, yet, there are several researches which characterize a very good theoretical, philosophical and methodological basis. Similarly, the analysis techniques of the geographers typify a vivid characteristic as used in other parts of the world.